Fractional exhaled nitric oxide (FeNO) among school children in Java and Sumatra, Indonesia: associations with respiratory symptoms, house dust mite sensitization and the home environment - Norbäck, Dan; Hashim, Jamal Hisham; Hashim, Zailina; Jalaludin, Juliana; Ismail, Rohaida; Wieslander, Gunilla; Wispriyono, Bambang; Sary, Lolita; Pratama, Satria; Sari, Meliana; Sisinta, Tiaraima; Putra, Hondli; et al. (Taylor and Francis Ltd., 2024)
Objective: To study associations between fractional exhaled nitric oxide (FeNO) and asthma, airway symptoms, sensitization to common allergens, outdoor pollution and home environment among 380 students in eight junior high schools in two areas in Indonesia. Methods: Data on health and home were collected by a face-to face interview before measuring FeNO and performing skin prick test against common allergens. Exploratory linear mixed and logistic regression models were employed. Results: Geometric mean of FeNO was 17.8 ppb (GSD 2.09) and 139 students (36.6%) had elevated FeNO (>20 ppb). In total, 107 students (28.2%) were sensitized to house dust mite (HDM) (Der p1 or Der f1), 4 (1.1%) to cat and 3 (0.8%) to mold (Cladosporium or Alternaria). Moreover, 20 students (5.3%) had diagnosed asthma, 38 (10.0%) had current wheeze, and 107 (28.2%) had current rhinitis. HDM sensitization, diagnosed asthma, current wheeze, and current rhinitis were associated with FeNO. In total, 281 students (73.9%) had mold or dampness, 232 (61.1%) had environmental tobacco smoke (ETS) and 43 (11.3%) had other odor at home. Indoor mold or dampness and other odor at home were associated with FeNO. ETS was negatively associated with FeNO. Conclusion: HDM sensitization and elevated FeNO can be common among children in this part of Indonesia. The high prevalence of elevated FeNO indicate that undiagnosed childhood asthma is common. Dampness, mold and odor at home can be associated with increased FeNO while ETS can be associated with decreased FeNO.